Motivations, barriers, and behaviors related to obtaining and discussing family health history: A sex-based comparison among young adults - Matthew Lee eSmith; Christopher E Beaudoin; Erica T Sosa; Jairus C Pulczinski; Marcia G Ory; E. Lisako J McKyer (Frontiers Media S.A., 2015)
Background: Genetic predisposition is a risk factor for many chronic diseases, yet little is known about the frequency in which college students seek out their family health history or with whom they communicate relevant information.Purpose: This study examines motivations and barriers associated with obtaining one's family health history and discussing it with others. Methods: Data were analyzed from 625 college students using an internet-delivered questionnaire. Questions asked respondents about intentions and motivations to obtain and share family health history as well as barriers encountered in obtaining family health history. Responses were bifurcated by participants' sex. Chi-squared and t statistics were used to identify response differences by sex. Results: Females were significantly more likely than males to be motivated to obtain their family health history, and more likely to have: shared their family health history with others; state they would share their family health history with others; and express a preference for sharing their family health history with a wider range of people. Discussion: Educational interventions and improved student health services could be effective mechanisms to increase college students' knowledge, awareness, and perceived importance of obtaining their family health history.